(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article analyzes the causes of the development of allergic diseases common among children - bronchial asthma and atopic dermatitis, the characteristics of their clinical symptoms and the dynamics of their course depending on age. It also highlights the role of parents and medical personnel in the early diagnosis, treatment and prevention of these diseases. The article examines the influence of external and internal factors, such as hygienic factors, hereditary predisposition, environmental pollution, on the development of the disease. It also presents scientifically based information on modern diagnostic methods and the effectiveness of treatment methods such as immunotherapy and diet therapy. Based on the results of the study, practical recommendations are given for strengthening children’s health and preventing allergic reactions.